2017
DOI: 10.1016/j.vetpar.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Presence and species identity of rumen flukes in cattle and sheep in the Netherlands

Abstract: The purpose of the study was to gain knowledge about the prevalence and identity of rumen flukes (RF) in cattle and sheep in the Netherlands. Routine faecal examinations of diagnostic submissions between May 2009 and September 2014 showed a mean annual herd or flock RF prevalence of 15.8% for cattle and 8.0% for sheep. Prevalence in cattle was higher after 2012 than before, which may reflect a change in detection method as well as an increase in true prevalence. During November and December 2014, an abattoir s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
20
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 22 publications
8
20
2
5
Order By: Relevance
“…A study in Ireland [18] confirmed a high prevalence of C. daubneyi in Irish sheep flocks, but also identified infection with another rumen fluke species, Paramphistomum leydeni, in a single animal. One case of P. leydeni infection in cattle has also been reported in the Netherlands [49]. This suggests that occasional infection from ruminant wildlife reservoir hosts, where P. leydeni has been identified previously [52], may also occur in livestock.…”
Section: New Developments and Discoveriesmentioning
confidence: 55%
See 1 more Smart Citation
“…A study in Ireland [18] confirmed a high prevalence of C. daubneyi in Irish sheep flocks, but also identified infection with another rumen fluke species, Paramphistomum leydeni, in a single animal. One case of P. leydeni infection in cattle has also been reported in the Netherlands [49]. This suggests that occasional infection from ruminant wildlife reservoir hosts, where P. leydeni has been identified previously [52], may also occur in livestock.…”
Section: New Developments and Discoveriesmentioning
confidence: 55%
“…Since Gordon et al [20] proposed C. daubneyi as the primary rumen fluke species infecting livestock in Britain in 2013, a number of studies have been conducted in the UK and Ireland, all of which have confirmed this finding using molecular approaches to species identification [46][47][48]. Studies across Western Europe, in the Netherlands [49], Belgium [50], Italy [51] and Spain [17] have also confirmed, using molecular tools, the predominant rumen fluke species identified in livestock to be C. daubneyi. A study in Ireland [18] confirmed a high prevalence of C. daubneyi in Irish sheep flocks, but also identified infection with another rumen fluke species, Paramphistomum leydeni, in a single animal.…”
Section: New Developments and Discoveriesmentioning
confidence: 99%
“…Möglich ist dies, da die vom Großen Leberegel Fasciola hepatica bekannte Zwischenwirtschnecke Galba truncatula im gemĂ€ĂŸigten Klima Europas mit entsprechender Feuchtigkeit weit verbreitet ist [27] [45]. Studien aus den vergangenen 20 Jahren zeigen vermehrte Nachweise von Pansenegeln, teilweise wurden sprunghafte PrĂ€valenzanstiege verzeichnet: 1999 in Frankreich [38], 2009 und 2012 in Irland [72] [73] sowie 2013 in den Niederlanden [51]. In Irland erhöhte sich 2012 sogar die MortalitĂ€t bei Rindern infolge Paramphistomidose [72].…”
Section: Diskussionunclassified
“…Die abrupten PrĂ€valenzanstiege sind außerdem deshalb kritisch zu sehen, weil aufgrund der Verwechslungsgefahr zwischen Pansenegeleiern und Eiern des Großen Leberegels ausreichende Erfahrung mit der Methodik Voraussetzung fĂŒr korrekte Ergebnisse ist [56]. In den Niederlanden wurde sogar Ende 2012 eine neue, hochsensitive koproskopische Methode eingefĂŒhrt, was wahrscheinlich zu einer verbesserten Erkennung von Pansenegeleiern gefĂŒhrt hat, sodass sich höhere PrĂ€valenzen ergaben als vorher [51].…”
Section: Diskussionunclassified
“…Rerata geometrik telur Paramphistoma tiap gram tinja juga berbeda secara signifikan pada desa yang berbeda (P<0,05) (Tabel 8). Prevalensi Paramphistomiasis pada daerah lain di Indonesia dan di negara lainnya bervariasi antara 259% (Satyawardhana 2017;Melaku & Addis 2012;GonzĂĄlez-Warleta et al 2013;Szmidt-AdjidĂ© et al 2000;Jones et al 2017;Ploeger et al 2017;Eslami et al 2011). Variasi prevalensi ini dapat terjadi karena perbedaan metode pemeliharaan, ukuran contoh, komposisi ternak, potensi biologi keong dan inang, serta iklim dan topografi lokasi pengambilan contoh (Chaudhary et al 2014).…”
Section: Paramphistoma: Prevalensi Dan Intensitas Infeksiunclassified